2008
DOI: 10.1186/bcr2192
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of prognostic signatures reveals the high predictive capacity of the Proliferation, Immune response and RNA splicing modules in breast cancer

Abstract: Introduction Several gene expression signatures have been proposed and demonstrated to be predictive of outcome in breast cancer. In the present article we address the following issues: Do these signatures perform similarly? Are there (common) molecular processes reported by these signatures? Can better prognostic predictors be constructed based on these identified molecular processes? Methods We performed a comprehensive analysis of the performance of nine gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
126
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(139 citation statements)
references
References 50 publications
(93 reference statements)
9
126
1
3
Order By: Relevance
“…Contrary to previous 'cancer stem cell' signatures, patients with ER-positive tumours expressing a 'mammosphere-derived' gene set had a significantly longer overall survival, independent of age, size, histological grade, lymph node status, ER, PR and HER2. This is not surprising, as outcome of patients with ER-positive disease has been shown to be largely determined by the expression levels of proliferation genes [31,104,111]. Furthermore, the 'mammospherederived' gene set did not show any discriminatory power in ER-negative breast cancers [110].…”
Section: Stem Cell Signaturesmentioning
confidence: 98%
See 1 more Smart Citation
“…Contrary to previous 'cancer stem cell' signatures, patients with ER-positive tumours expressing a 'mammosphere-derived' gene set had a significantly longer overall survival, independent of age, size, histological grade, lymph node status, ER, PR and HER2. This is not surprising, as outcome of patients with ER-positive disease has been shown to be largely determined by the expression levels of proliferation genes [31,104,111]. Furthermore, the 'mammospherederived' gene set did not show any discriminatory power in ER-negative breast cancers [110].…”
Section: Stem Cell Signaturesmentioning
confidence: 98%
“…The 'wound-response signature' (ie CSR) was shown to be an independent predictor of metastasis and outcome in the NKI295 dataset, improved risk stratification based on the NIH or St. Gallen consensus criteria and identified patients with 'low risk' in the group of 'high-risk' patients stratified according to the NIH or St. Gallen guidelines [115]. Despite the alleged removal of cell cycle-related genes from the CSR, the wound-response signature was still found to be significantly enriched for proliferation genes [31,111].…”
Section: Fibroblast Signaturesmentioning
confidence: 99%
“…The expression level of immune response genes has recently been shown to provide prognostic value for sporadic ER-negative breast tumours (Teschendorff et al, 2007) and this biological process seems to be commonly present in breast cancer prognosis signatures (Reyal et al, 2008). Examination of gene-set #2 and the signature of Teschendorff et al (2007) identified 18 genes in common, which is higher than the number expected by chance (P-value o10 À7 ).…”
Section: Putative Prognostic Value Of the Immune Responsementioning
confidence: 98%
“…Recently, several groups have identified a subgroup of good prognosis ERÀ cancers, encompassing a subgroup of triple-negative and basal-like tumors, which is characterized by the expression of an immune response module. [125][126][127][128] This transcriptomic profile may prove helpful for the identification of patients with triple-negative and basal-like cancers that have a better outcome. In this context, the finding of higher expression of CT-X antigens (in particular MAGE and NY-ESO) in this subgroup opens up another potential avenue for therapy as vaccines against these antigens are already in clinical trial for lung cancer.…”
Section: Clinical Behavior Of Basal-like and Triple-negative Breast Cmentioning
confidence: 99%